2001
DOI: 10.1097/00005373-200106000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Management of Midclavicular Fractures: Comparison between Nonoperative Treatment and Open Intramedullary Fixation in 80 Patients

Abstract: According to our experience, we conclude that nonoperative treatment appears more advantageous than open intramedullary fixation for the management of most midclavicular fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(77 citation statements)
references
References 17 publications
1
67
0
9
Order By: Relevance
“…Fractures of the clavicle are among the most common skeletal injuries, and they are usually treated conservatively [1,2]. Surgical treatment may be strongly indicated in cases with open fractures, vascular compromise, progressive neurological deficit and cases with floating shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…Fractures of the clavicle are among the most common skeletal injuries, and they are usually treated conservatively [1,2]. Surgical treatment may be strongly indicated in cases with open fractures, vascular compromise, progressive neurological deficit and cases with floating shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…14,[23][24][25][26][27][28][29][30][31][32] In addition, 6 studies included treatment of nonunions or delayed unions and did not make a distinction with the treatment of acute fractures when describing the complications, 16,33-37 2 studies were surgical technique papers, 38,39 1 study reported on plate fixation, 40 1 study lacked a definition for dislocation, 41 1 study did not make a distinction between angulation and comminution, 42 1 study included fewer than 10 patients 15 and, in 1 study, 11 authors reported on a previously reported patient population. Reported rates for major complications like bonehealing problems and deep infections requiring implant removal were no higher than 7%.…”
Section: Discussionmentioning
confidence: 99%
“…Eight complications occurred in 16 patients: three cases of posterior skin breakdown due to prominent hardware, two cases of hardware breakage, two cases of decreased sensation over insertion site, and one case of persistent pain. Grassi et al [6] compared nonoperative treatment to open intramedullary fixation of midclavicular fractures and concluded nonoperative treatment was superior due to the much lower complication rate. The intramedullary fixation group experienced eight superficial infections, three refractures, two delayed unions with pin breakage, and two nonunions.…”
Section: Discussionmentioning
confidence: 99%